The New Generation of Attitude Determination Sensor for LEO Satellite based on Induced Electric Field - mohsen rezaei; Kamran Charmacani; hamed Hashemi Mehne; Yaser Norouzi (AUT Journal of Electrical Engineering, 2022)
Many satellites use closed-loop attitude control to carry out their missions. They use several sensors such as sun, magnetometer, and star tracker to close the control loop. Sun sensors are not operational during the eclipse and therefore, one of the observed vectors is lost.  For this reason, attitude determination in eclipse can be a challenging issue for control engineers. This paper presents a novel idea for producing a new generation of sensors that can measure the induced electric field vector not only in eclipse, but also in all orbit. This electric field comes from a high velocity of the spacecraft in the magnetic field of the Earth. This vector is always perpendicular to the magnetic field; thus, it is never aligned with the magnetic vector and never causes singularity and accuracy decrease. The induced electric field is measured by three RC circuits[1] that are actuated by sinusoidal voltage. The dielectrics of the capacitors are made of ferroelectric materials; therefore, the induced voltage affects the permittivity and voltage of the capacitor. By measuring and calibrating this effect in three perpendicular axes, we can measure the three components of the electric field vector. The theory of the proposed sensor has been developed, and simulation studies validate the results. [1] resistor-capacitor circuit